Textbook on the Philippine constitution - De Leon, Hector S. (Quezon City : Rex BookStore, 1997)
As the Supreme law of the land, the constitution is by no means self- explanatory. Yet it is so important a document with which every citizen should be familiar as it directly and constantly touches every aspect of his everyday life; indeed, to be respected, obeyed and defended if our nation must grow and survive. This is the reason for the requirement that all educational institutions shall include the study of the constitution as part of the curricula.
Introduction -- Preamble -- Article I- The National Territory -- Article II- Declaration of Principles and State Policies -- Article III- Bill of Rights -- Article IV- Citizenship -- Article V- Suffrage -- Article VI- Legislative Department -- Article VII- Executive Department -- Article VIII- Judicial Department -- Article IX- Constitutional Commissions -- Article X- Local Government -- Article XI- Accountability of Public Officers -- Article XII- National economy and Patrimony -- Article XIII- Social Justice and Human Rights -- Article XIV- Education, Science and Technology, Arts, Culture and Sports Education -- Article XV- The Family -- Article XVI- General Provisions -- Article XVII- Amendments or Revisions -- Article XVIII- Transitory Provisions.
Keywords: PHILIPPINES -- CONSTITUTIONS